2020
DOI: 10.3329/ptcb.v30i1.47793
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficiency Analysis of Different Explants and Contribution of Polyamines on in vitro Propagation of Dendrobium Hybrid Sonia

Abstract: An efficient method of plant regeneration and subsequent growth and development of Dendrobium hybrid Sonia was developed using intact seedling, shoot tip and thin cell layer. Maximum number of PLBs was obtained in MS liquid medium supplemented with 0.5 mg/l NAA and 1mg/l BAP through shoot tip and thin cell layer culture (TCL). Highest number of adventitious shoot formation was recorded in 0.5 mg/l of NAA and 2 mg/l of BAP through shoot tip culture. In shoot tip and TCL cultures, the necrosis was checke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
2
1
Order By: Relevance
“…It was observed that when MS medium supplemented with the combination of BAP and NAA, stimulated the formation of EC after 6 weeks of culture and further development of SEs were observed in lower concentrations. This finding could be corelated with the effect of BAP and NAA to induce maximum number of PLBs from thin cell layer culture of Dendrobium hybrid Sonia (Mandal et al 2020). The similar synergistic effect of BAP and NAA were also reported in Dendrobium palpebrae (Bhowmik and Rahman, 2020) and Cymbidium finlaysonianum (Shahinul Islam et al 2015).…”
Section: Pyatisupporting
confidence: 77%
See 1 more Smart Citation
“…It was observed that when MS medium supplemented with the combination of BAP and NAA, stimulated the formation of EC after 6 weeks of culture and further development of SEs were observed in lower concentrations. This finding could be corelated with the effect of BAP and NAA to induce maximum number of PLBs from thin cell layer culture of Dendrobium hybrid Sonia (Mandal et al 2020). The similar synergistic effect of BAP and NAA were also reported in Dendrobium palpebrae (Bhowmik and Rahman, 2020) and Cymbidium finlaysonianum (Shahinul Islam et al 2015).…”
Section: Pyatisupporting
confidence: 77%
“…This is advantageous to pharmaceutical industry that uses orchids as raw material in bulk quantity. Different plant tissues such as shoot tips (Mamun et al 2018;Mandal et al 2020) protocorm like bodies (Ashok Pyati 2020, Klaocheed et al 2021) pseudobulbs (Bowmik and Rahman 2020), nodal explants (Bhattacharyya et al 2016, Kaur 2017, leaf and roots (Lee and Chen 2014) stem thin cell layers (Parthibhan et al 2018) have been widely used as explants to obtain regenerative plantlets in several Dendrobiums. In D. ovatum different tissue culture systems for micropropagation have been established using mature and immature seeds as explants (Gurudeva 2019, Deeksha Raj et al 2021, Shetty et al 2015, Thejaswini and Narasimhan, 2017, Pujari et al 2021, Mary and Divakar 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of PAs (1.0 µM of Put and Spd) to liquid MS medium induced direct PLB formation with a highest frequency of 80%, and associated with 8 µM BA enhanced the direct PLB formation in shoot tip culture of Dendrobium hybrid Sonia. While the control with only 8 µM BA showed no direct PLB formation of Dendrobium(Mandal et al 2020), in the present study, using the same concentration of BA, 89% of PLBs regeneration with apical tTCLs was obtained. We only evaluated the responses of PGRs and isolated PAs, requiring experiments of the combination to verify the effect on the PLBs regeneration of C. warneri.…”
contrasting
confidence: 48%
“…al) added with TDZ (1.0 mg/l) and NAA (0.5 mg/l) induced callus frequency of 77.8% (Ahmed Sherif et al 2016). The thin cell layer culture in Dendrobium Hybrid Sonia induced maximum frequency of callus formation (40%) in MS medium supplemented with NAA (0.5 mg/l) with BAP (0.5 mg/l) (Mandal et al 2020). Until there are many reports about plantlet regeneration from callus cultures via PLB formation in many orchids.…”
Section: Resultsmentioning
confidence: 99%